Characterization of recrystallized itraconazole prepared by cooling and anti-solvent crystallization - Pornsak Sriamornsak; Kanokporn Burapapadh (Elsevier, 2015)
The objective of the present study was to alter the crystal habit of itraconazole (ITZ) by cooling and anti-solvent crystallization and characterize its properties. ITZ was recrystallized in different solvents and the effects of each solvent on morphology of crystals, dissolution behavior and solid state of recrystallized drug particles were investigated. The results revealed that ITZ crystals recrystallized by cooling and anti-solvent crystallization showed the different crystal habits from the untreated ITZ. Using cooling crystallization tended to provide needle-shaped crystals while the crystals obtained from anti-solvent crystallization showed more flaky, plate shape. This indicated the importance of preparation method on nucleation and crystal growth. No change in drug polymorphism was observed, according to determination of thermal property and crystalline state by differential scanning calorimetry and powder X-ray diffractometry, respectively. The recrystallized ITZ showed higher drug dissolution than untreated ITZ and the highest drug dissolution was observed from the samples recrystallized in the presence of PEG 200, which provided the small plate-shaped crystals with tremendously increased in surface area. However, the increasing of drug dissolution is relatively small, therefore, further development may be required.